Surveillance and prevention culicidae vectors - the portuguese case - Paixão, Susana (2017)
Introduction: Dengue and Zika are considered a disease of the XXI re-emerging century are a major public health problems in the world, not only because it affects thousands of people, since the mosquito Aedes aegypti tends to reproduce in homes but also because it is considered one of the most important viral diseases transmitted by animals. Health surveillance for Environmental Health of the environment, and its mission is to analyze, prevent and correct the health risks, which are environmental or potential. It is in this sense that environmental health is as important to end this disease, and in the meantime to prevent it does not affect human health. Objetives: Tracking the presence of Culicidae Vectors in Portugal. Methods: The study is based on data from DGS program and INSA, Revive, which plating the presence of mosquitoes and larvae that can cause contamination and diseases originating from mosquitoes, the analysis of these data and the other allows us to see the need for prophylactic care to have in our country, especially in Madeira, which, for its location and climate can foster the emergence of these. Results: Samples and data collected by the REVIVE program did not detect the presence of the virus mosquitoes in continental Portugal, however climate change that Portugal crosses can cause the onset of mosquito vectors of carriers, so you want to public education for preventive measures can combat the proliferation of mosquitoes mosquito carriers. Conclusions: Although there are no mosquitoes, as educate the public for mosquito prevention measures. Thus, this study provides a number of solutions to minimize the proliferation mosquito vectors.